1996
DOI: 10.1109/20.538808
|View full text |Cite
|
Sign up to set email alerts
|

Tribological implications of solvents in dip-coating lubrication of thin film magnetic disks

Abstract: In this paper, we show that for ultra thin lubricant films (-2 nm) the solvent used in dip-coating of thin film magnetic disks may have a significant effect on the tribological performance of the disk. Two solvents are used in this study. A large difference in CSS performance at 80% humidity is found between using the two solvents. The solvent effect (evaporation, diffusion & adsorption) is believed to determine how lubricant molecules are deposited onto disk surfaces causing different microstructure or confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The dip coating solution concentration, draw rate, vapor head space, and solvent also play a role in determining the properties and performance of the film. Both Gao et al [18] and Waltman et al [19] studied the effect of dip coating solvent on tribological performance. Only Gao et al [16] reported some effect of the film microstructure on tribological performance at the relative humidity of 80%.…”
Section: Experimentation and Mesoscopic Analysismentioning
confidence: 98%
“…The dip coating solution concentration, draw rate, vapor head space, and solvent also play a role in determining the properties and performance of the film. Both Gao et al [18] and Waltman et al [19] studied the effect of dip coating solvent on tribological performance. Only Gao et al [16] reported some effect of the film microstructure on tribological performance at the relative humidity of 80%.…”
Section: Experimentation and Mesoscopic Analysismentioning
confidence: 98%
“…They attributed the difference to the microstructure and/or orientation of the lubricant molecules affected differently by the solvent [1]. Lubricants topi- Figure 7.…”
Section: Summary and Concluding Remarksmentioning
confidence: 98%
“…Most intriguingly Chao et al reported that, keeping all other factors constant, the disk performance (measured by the CSS test) could vary significantly depending on the choice of the solvent used in the dip-coating process. They attributed the observed difference to the microstructure and/or orientation of the lubricant molecules affected differently by the solvent employed in the dip-coating process [1].…”
Section: Introductionmentioning
confidence: 98%